Copy Number Gains of VPS72 Drive De Novo Lipogenesis and Hepatocarcinogenesis via ATF3/mTORC1/SREBP1 Axis - Qinglin Zhang; Yunxing Huang; Yin Tong; Kenneth Tsz Chun Ng; Jiangwen Zhang (Advanced Science)
Abstract Hepatocellular carcinoma (HCC) is the predominant form of primary liver cancer and a major contributor to cancer‐related mortality globally. Central to its pathogenesis is the dysregulation of lipid metabolism in hepatocytes, leading to abnormal lipid accumulation. Our bioinformatics analysis has identified the histone acetyltransferase complex subunit VPS72 as being associated with HCC, yet the precise molecular mechanisms through which VPS72 contributes to hepatocarcinogenesis remain poorly understood. Our analysis of extensive HCC patient cohorts identifies a significant proportion with VPS72 copy number gains, which are strongly linked to adverse prognostic outcomes. By integrating RNA‐Seq, ChIP‐Seq, ATAC‐seq, and experimental validation, we show that VPS72 overexpression activates mTORC1 signaling, subsequently promoting lipid synthesis and driving HCC progression. We further uncover that VPS72 modulates the epigenetic landscape by enhancing DNA methylation at the ATF3 promoter, resulting in ATF3 repression and subsequent activation of mTORC1. This study elucidates a novel regulatory axis that links dysregulated lipid metabolism with HCC progression, highlighting potential epigenetic and metabolic targets for therapeutic intervention.